ANALASIS PENGARUH BAURAN PEMASARAN (PRODUK, HARGA, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOMSUMEN DI MINIMARKET ALFAMART ATAU INDOMARET : STUDI KASUS MAHASISWA/I INSTITUT AGAMA ISLAM TAZKIA - Nurfatimah, Saktia Siti; Wahilda.E, Syahzila; Azmi, Nafizatul; Zaerofi, Afif (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Minimarkets in Indonesia increased from 2015 to 2020 by 39 percent. The number increased from 26,102 outlets in 2015 to 36,146 outlets in 2020. In 2020, the two largest minimarkets in Indonesia, Indomaret and Alfamart, each had 18,271 outlets, respectively. Alfamart and Indomaret can meet almost all customer needs, both primary and secondary needs. This product has good quality and competitive price. In addition, the location of these two convenience stores, which can be found in almost every place, is the most prominent. This study used a quantitative descriptive method conducted on respondents who had made purchases at Alfamart or Indomaret. The purpose of this study is to determine whether products, prices, locations, and promotions affect purchasing decisions for IAI Tazkia Bogor students. The population in this study is IAI Tazkia students who shop at Alfamart or Indomaret. The method used in sampling in this study is purposive sampling through the distribution of questionnaires with google forms. The data analyzed are instrument tests, classical assumption tests, static tests, and multiple linear regression tests.